Tripability Analysis of Casing Strings in Directional Wells Using the Continuous Beam-Column and Buckling Theory. (31st July 2022) - Wang, Gang; Liu, Gang; Wang, Kai; Li, Yichen; Hu, Yinan
Abstract : Hindered casing strings are often encountered in unconventional oil and gas exploration during the casing running process. This not only increases the operating costs and time but can also lead to downhole accidents and even abandonment in serious cases. Due to various assumptions, the calculation results of the existing soft models and hard models are different, which causes confusion for field operators when taking friction reduction measures. Moreover, a lowering force is often applied to assist hindered casing string running in a drilling field. However, its application is mainly based on work experience and lacks mechanistic analysis and theoretical guidance. Thus, in this study, a simulation model for the analysis of casing string tripability in a directional well was established and the model was combined with the continuous beam-column theory and buckling theory. The model was used to study how various factors including the friction coefficient, drilling fluid density, and casing diameter could affect the lowering force required when a casing string was hindered by buckling. The results showed that the maximum lowering force and the maximum effective lowering force decreased with the increase in the friction coefficient and the performance of the drilling fluid could be adjusted rapidly, which would be beneficial for ensuring that the casing string could be tripped smoothly by applying a lowering force. The increase in the drilling fluid density caused the maximum lowering force and the maximum effective lowering force to decrease, which was not conducive to hindered casing string running. The larger the casing diameter was, the greater the maximum lowering force and the maximum effective lowering force were. It was more convenient to apply a lowering force for a casing with a large diameter. In addition, the improved model could identify whether the casing string was in contact with the upper or lower borehole walls. Through finite element method verification, the prediction was in line with the actual casing running operation and the improved model has the smallest prediction error, i.e., 6.58%, compared with the existing models. Therefore, the improved model might provide necessary theoretical guidance for casing running operations in directional wells.